Analisis Penerapan Manajemen Pengetahuan di Direktorat Jenderal Pengelolaah Pembiayaan dan Risiko Kementerian Keuangan Republik Indonesia - Fahrur Ridho; Yeni Absah; Meilita Tryana Sembiring (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
Knowledge management at the Directorate General of Budget Financing and Risk Management (DJPPR) has been institutionalized through Echelon IV units within each directorate. This initiative aims to facilitate smooth inter-Echelon I rotation as part of the "KemenkeuSatu" framework, while simultaneously preserving the expertise of specialists and retiring officials. This study aims to analyze the implementation of knowledge management at DJPPR, identify existing barriers, and formulate key success factors for the future. Utilizing a qualitative descriptive method, data were collected through field observations, in-depth interviews with 19 informants, and questionnaires distributed to 224 DJPPR employees. The results indicate that knowledge management implementation at DJPPR is performing well, with an average score of 3.95. The "knowledge application and use" dimension achieved the highest score (4.23), followed by "knowledge sharing" (4.16) and "knowledge creation" (3.75), while the "knowledge capture and storage" dimension recorded the lowest score (3.68). The study also identifies primary barriers stemming from human resources, organizational support, and leadership involvement. Conversely, the key success factors include human resource aspects (awareness, competence, and a learning mindset), organizational support (governance, rewards, technology, and budget), leadership support, and cultural factors (trust and a sharing culture).